A Study on the Feasibility of Utilizing Heater-Generated Temperature in a Semi-Automatic Mango Stirring Machine - Saenpong, Anuwat; Kraisoda, Pakkip; Jansawang, Sawanee; Lawbootsa, Siwanu; Sasen, Chailai (Journal of Engineering and Industrial Technology, Kalasin University, 2025)
This research aims to study the suitability of temperature from heaters used in semi-automatic mango stirrers. The temperature tests were tested at 90, 100, 110 and 120°C to study the effects on the properties of stirred mangoes, including viscosity (Pa·s), weight (grams) and percentage moisture (%wb). The experiment was conducted using 2,000 grams of MAHACHANOK (Mangifera indica L.) MANGO and stirring continuously at intervals of 30, 60, 90 and 120 minutes. The experimental setup consisted of a 22-inch diameter stirring pan, which was rotated at a fixed speed of 15 rpm. The heating process was performed using a 2,500-watt electric heater to maintain the required thermal conditions. The results showed that the temperature and time used for stirring significantly influenced the quality of the stirred mangoes. For the reason, higher temperatures accelerate the evaporation of water. As a result, moisture decreases and viscosity increases. The temperature of 110°C and the stirring time of 90 minutes are the optimal values for the weight after stirring at 730 grams. This is because the viscosity value is close to the reference value of 0.498 Pa·s and the percentage moisture is at an appropriate 70.32%wb. However, optimum temperature control and stirring time are important factors for product quality.